KONSEP RESTORATIF JUSTICE DALAM SISTEM PEMIDANAAN PADA PERADILAN MILITER - Nugroho Muhammad Nur; Audyna Mayasari Muin (LPPM Universitas Ekasakti Padang, 2023)
Restorative justice is an alternative approach to criminal resolution that focuses on restoring harm caused by the committed crime for the benefit of the victim, offender, and community. It aims to rebuild the damaged relationships resulting from the crime by addressing the incurred harm, restoring justice for the victim, and providing the offender an opportunity to acknowledge their mistake and make amends to the community. Implementing restorative justice in the Military Justice system can be achieved by strengthening and developing mediation mechanisms as an alternative means of resolving criminal offenses. Mediation can involve various parties, such as the victim, offender, family, and community. The research method employed in this study is normative research. The problem approach in this study involves using a legislative approach and a conceptual approach. The resolution of criminal offenses through restorative justice mechanisms in the Military Justice system can be implemented by considering the principles of justice, utility, and legal certainty. The concept of restorative justice in the Military Justice system can be implemented through two methods, namely through the Formulation of Military Justice System Regulations and Mediation.